Convergence in TFP among Italian Regions - Panel Unit Roots with Heterogeneity and Cross Sectional Dependence - Joseph Byrne; Giorgio Fazio; Davide Piacentino (European Regional Science Association (ERSA), 2005)
This paper performs a number of tests to estimate convergence in total factor productivity (TFP) among Italian regions during the period 1970-2001. We generate the regional TFP series using growth accounting methodologies, and then apply a range of panel unit root tests to analyse the process of convergence. We extend the existing literature by incorporating three main improvements. Firstly, we control for the heterogeneity arising from the different economic structure of each region. Secondly, we account for the cross-sectional dependence due to common shocks or spillovers among different regions at the same time. Finally, we look for clubs of convergence using tests of poolability both on economic and statistical grounds.
Keywords: 330